Laminate, image display member and manufacturing method therefor, and mobile electronic device and manufacturing method therefor
By using resin film and adhesive laminate with moderate total light transmittance in mobile electronic devices, the impact resistance and inspection problems of equipment are solved, and excellent anti-reflection and inspection properties are achieved, and suitable for image display components and Manufacturing of mobile electronic devices.
Patent Information
- Application Number
- CN202411434738.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2020-08-05
- Filing Date
- 2021-07-02
- Publication Date
- 2024-12-20
AI Technical Summary
In existing mobile electronic devices, after excluding thick black cushioning materials, the impact resistance of the organic EL display is reduced, and the appearance and foreign object inspection properties performed from the back side are reduced, which cannot effectively prevent incident light reflection.
A laminated body consisting of a resin film, an adhesive layer and another resin film has a total light transmittance of between 20% and 83%, and is used to manufacture an image display member and a mobile electronic device, and peel the resin The film is applied to the adhesive layer and the OLED panel is bonded to the structure of the adhesive layer and the resin film to achieve excellent anti-reflectivity and inspection properties.
Excellent anti-reflectiveness from the viewing side and excellent inspection from the back side in the mobile electronic device are achieved, and the impact resistance of the equipment and the needs of the manufacturing process are met.
Smart Images

Figure CN119159883A_ABST
Abstract
Description
[0001] This application is a divisional application of an application with an application date of July 2, 2021, an application number of 202180058411.4, and an invention name of a laminate, an image display component and a method for manufacturing the same, and a mobile electronic device and a method for manufacturing the same. Technical Field
[0002] The present invention relates to a laminate. Typically, the present invention relates to a laminate that can be suitably used to fix internal components of a mobile electronic device, prevent surface damage, reinforce the device, etc. The present invention also relates to a method for manufacturing an image display component using the laminate, and a method for manufacturing a mobile electronic device using the laminate. Background Art
[0003] Generally, adhesive tapes such as surface protection films (SPV) and reinforcement films (RF) are used in the internal components of mobile electronic devices for fixing, preventing surface damage, and reinforcing the components (eg, Patent Document 1).
[0004] In recent years, organic EL displays have been widely used in mobile electronic devices. Organic EL displays are extremely thin and easily damaged components, so thick buffer materials are used to protect the back of organic EL displays for the purpose of absorbing impacts such as falling. Furthermore, in order to prevent incident light from being reflected from the viewing side, black buffer materials are generally used as the buffer material to absorb the incident light.
[0005] Recently, as mobile electronic devices tend to be thinner, there is an increasing demand for mobile electronic devices equipped with an organic EL display that excludes a thick black buffer material from the back surface.
[0006] The reduction in the impact resistance of the organic EL display due to the elimination of the thick black buffer material can be addressed by a new design such as improving the impact resistance of the housing.
[0007] However, if the thick black buffer material is excluded, there is a problem that the incident light cannot be absorbed from the observation side, and the incident light is directly reflected on the observation side, so that the inside of the mobile electronic device can be observed.
[0008] On the other hand, in order to prevent the inside of the mobile electronic device from being observed, a thin member with low transmittance that can fully absorb incident light may be arranged on the back of the organic EL display. However, in this case, the inspection performance such as appearance inspection and foreign matter inspection from the back side may be reduced during the manufacturing process.
[0009] Prior art literature
[0010] Patent Literature
[0011] Patent Document 1: Japanese Patent Application Publication No. 2016-17109 Summary of the invention
[0012] Problem that the invention aims to solve
[0013] The subject of the present invention is to provide a laminated body that can be suitably used in a mobile electronic device having an image display panel, the laminated body can exhibit excellent anti-reflection properties for preventing reflection from the viewing side and excellent inspection properties for inspection from the back side. In addition, a method for manufacturing an image display component using the laminated body and a method for manufacturing a mobile electronic device using the laminated body are provided.
[0014] Solutions for solving problems
[0015] The laminate according to the embodiment of the present invention is a laminate having three or more layers, namely, a resin film (1), an adhesive layer (1), and a resin film (2) in this order.
[0016] The total light transmittance of the laminate is 20% to 83%.
[0017] The method for producing an image display member according to an embodiment of the present invention is a method for producing an image display member using the above-mentioned laminate, wherein:
[0018] The resin film (1) is directly laminated with the adhesive layer (1).
[0019] The manufacturing method comprises:
[0020] A step of peeling the resin film (1) from the adhesive layer (1); and
[0021] A step of laminating an OLED panel onto the exposed adhesive layer (1).
[0022] The method for manufacturing a mobile electronic device according to an embodiment of the present invention is a method for manufacturing a mobile electronic device using the above-mentioned laminate, wherein:
[0023] The resin film (1) is directly laminated with the adhesive layer (1), and the manufacturing method comprises:
[0024] A step of peeling the resin film (1) from the adhesive layer (1);
[0025] A step of laminating an OLED panel on the exposed adhesive layer (1);
[0026] A step of providing an adhesive layer (2) on the outermost layer of the laminate on the side of the resin film (2) as viewed from the adhesive layer (1); and
[0027] A step of bonding a housing to the side of the adhesive layer (2) opposite to the side where the resin film (2) is present.
[0028] Effects of the Invention
[0029] According to the present invention, a laminated body that can be suitably used in a mobile electronic device having an image display panel can be provided, and the laminated body can exhibit excellent anti-reflection properties for preventing reflection from the viewing side and excellent inspection properties for inspection from the back side. In addition, a method for manufacturing an image display component using the laminated body and a method for manufacturing a mobile electronic device using the laminated body can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a schematic cross-sectional view of one embodiment of the laminated body of the present invention.
[0031] Figure 2 This is a schematic cross-sectional view of another embodiment of the laminated body of the present invention.
[0032] Figure 3 It is a schematic cross-sectional view showing the confirmation direction of the anti-reflection property confirmation.
[0033] Figure 4 It is a schematic cross-sectional view showing the confirmation direction of the inspection confirmation. DETAILED DESCRIPTION
[0034] In the present specification, when the expression "weight" appears, it can be replaced with "mass" which is a commonly used SI unit expressing weight.
[0035] In this specification, when the expression "(meth)acrylic acid" exists, it means "acrylic acid and / or methacrylic acid", when the expression "(meth)acrylate" exists, it means "acrylate and / or methacrylate", when the expression "(meth)allyl" exists, it means "allyl and / or methallyl", and when the expression "(meth)acrolein exists, it means "acrolein and / or methacrolein".
[0036] 《《1.Laminated body》》
[0037] The laminate according to the embodiment of the present invention is a laminate having three or more layers, namely, a resin film (1), an adhesive layer (1), and a resin film (2) in this order.
[0038] The laminated body according to the embodiment of the present invention may have any and appropriate other layers within the range that does not impair the effect of the present invention, as long as it has a resin film (1), an adhesive layer (1), and a resin film (2) in this order. Such other layers may be only one layer or may be two or more layers.
[0039] The laminated body according to the embodiment of the present invention is preferably a resin film (1), an adhesive layer (1) and a resin film (2) directly laminated in this order. However, any and appropriate other layers may be provided between the resin film (1) and the adhesive layer (1) or between the adhesive layer (1) and the resin film (2) within the scope that does not impair the effect of the present invention. Such other layers may be only one layer or may be two or more layers.
[0040] In the laminate according to the embodiment of the present invention, it is preferred that the resin film (1) and the resin film (2) are respectively the outermost layers.
[0041] The number of layers stacked in the laminate according to the embodiment of the present invention is preferably 3 to 10, more preferably 3 to 8, further preferably 3 to 5, and particularly preferably 3.
[0042] The total thickness of the laminate according to the embodiment of the present invention is preferably 75 μm to 400 μm, more preferably 100 μm to 350 μm, further preferably 120 μm to 300 μm, and particularly preferably 140 μm to 240 μm.
[0043] One embodiment of the laminate of the present invention is a three-layer laminate in which a resin film (1), an adhesive layer (1) and a resin film (2) are directly laminated in this order. Specifically, Figure 1 As shown, the laminated body 100 of the present invention is obtained by directly laminating a resin film (1) 10, an adhesive layer (1) 20, and a resin film (2) 30 in this order.
[0044] exist Figure 1 In one embodiment of the laminate of the present invention shown above, the resin film (1) may form a separator.
[0045] The laminate according to the embodiment of the present invention is as follows Figure 1 As shown, when the three-layer laminate is a resin film (1), an adhesive layer (1) and a resin film (2) directly laminated in sequence, the total thickness is preferably 45 μm to 300 μm, more preferably 60 μm to 250 μm, further preferably 70 μm to 200 μm, and particularly preferably 85 μm to 150 μm.
[0046] Another embodiment of the laminate of the present invention is a five-layer laminate in which a resin film (1), an adhesive layer (1), a resin film (2), an adhesive layer (2), and a resin film (3) are directly laminated in this order. Specifically, Figure 2 As shown, the laminate 100 of the present invention is composed of a resin film (1) 10, an adhesive layer (1) 20, a resin film (2) 30, an adhesive layer (2) 40, and a resin film (3) 50 directly laminated in this order.
[0047] exist Figure 2 In another embodiment of the laminate of the present invention shown below, the resin film (1) may form a separator.
[0048] The laminate according to the embodiment of the present invention is as follows Figure 2 As shown, when the five-layer laminate is directly stacked in sequence including a resin film (1), an adhesive layer (1), a resin film (2), an adhesive layer (2) and a resin film (3), the total thickness is preferably 75 μm to 400 μm, more preferably 100 μm to 350 μm, further preferably 120 μm to 300 μm, and particularly preferably 140 μm to 240 μm.
[0049] As other layers, from the viewpoint of being able to further demonstrate the effect of the present invention, for example, a transmittance control layer can be listed. As the transmittance control layer, any and appropriate layer can be used as long as it is a layer that can control the transmittance. As such a transmittance control layer, for example, a black tape layer, a black printed layer, etc. can be listed.
[0050] The transmittance control layer may include, for example, the surface of the resin film (1) on the opposite side to the adhesive layer (1), the surface of the resin film (1) on the adhesive layer (1) side, the surface of the adhesive layer (1) on the resin film (1) side, the surface of the adhesive layer (1) on the resin film (2) side, the surface of the resin film (2) on the adhesive layer (1) side, the surface of the resin film (2) on the adhesive layer (2) side, the surface of the adhesive layer (2) on the resin film (2) side, the surface of the adhesive layer (2) on the resin film (3) side, the surface of the resin film (3) on the adhesive layer (2) side, the surface of the resin film (3) on the opposite side to the adhesive layer (2), etc.
[0051] The total light transmittance of the laminated body described in the embodiment of the present invention is 20% to 83%, preferably 30% to 83%, more preferably 50% to 83%, and particularly preferably 60% to 83%. If the total light transmittance of the laminated body described in the embodiment of the present invention is adjusted to the above range, it is preferably possible to form a laminated body that can be suitably used in a mobile electronic device having an image display panel, and the laminated body can exhibit excellent anti-reflection properties for preventing reflection from the observation side and excellent inspection properties for inspection from the back side. If the total light transmittance of the laminated body described in the embodiment of the present invention deviates from the above range and is too low, the inspection properties for inspection from the back side may be reduced. If the total light transmittance of the laminated body described in the embodiment of the present invention deviates from the above range and is too high, the anti-reflection properties for preventing reflection from the observation side may be reduced.
[0052] 《1-1. Resin film (1)》
[0053] From the viewpoint of further demonstrating the effects of the present invention, the thickness of the resin film (1) is preferably 20 μm to 100 μm, more preferably 20 μm to 80 μm, further preferably 20 μm to 70 μm, particularly preferably 20 μm to 60 μm, and most preferably 25 μm to 50 μm.
[0054] The resin film (1) includes a resin base film (1a).
[0055] Examples of the resin substrate film (1a) include plastic films made of polyester resins such as polyethylene terephthalate (PET), polyethylene naphthalate (PEN), and polybutylene terephthalate (PBT); plastic films made of olefin resins having α-olefins as monomer components such as polyethylene (PE), polypropylene (PP), polymethylpentene (PMP), ethylene-propylene copolymers, and ethylene-vinyl acetate copolymers (EVA); plastic films made of polyvinyl chloride (PVC); plastic films made of vinyl acetate resins; and plastic films made of polycarbonate. Plastic films composed of polytetrafluoroethylene, polychlorotrifluoroethylene, polyvinyl fluoride, polyvinylidene fluoride, tetrafluoroethylene-hexafluoropropylene copolymer, chlorofluoroethylene-vinylidene fluoride copolymer, etc.
[0056] The resin base film (1a) may be composed of only one layer or two or more layers. The resin base film (1a) may be stretched.
[0057] The resin substrate film (1a) may be subjected to a surface treatment, such as corona treatment, plasma treatment, chromic acid treatment, ozone exposure, flame exposure, high voltage electric shock exposure, ionizing radiation treatment, primer coating treatment, and the like.
[0058] The resin substrate film (1a) may include any and appropriate additives within the scope of not damaging the effect of the present invention. Such additives may be only one, or may be more than two. However, from the viewpoint of being able to further show the effect of the present invention, the additive content in the resin substrate film (1a) is preferably less than 5% by weight, more preferably less than 3% by weight, further preferably less than 1% by weight, particularly preferably less than 0.5% by weight, and most preferably substantially 0% by weight. Here, "substantially 0% by weight" refers to the trace impurity content within the scope of not damaging the effect of the present invention that can be ignored.
[0059] As the additive, for example, at least one selected from the group consisting of a coloring pigment and a coloring dye can be cited. As the coloring pigment, a black pigment can be preferably cited. As the coloring dye, a black dye can be preferably cited.
[0060] When the resin base film (1a) contains at least one selected from the group consisting of coloring pigments and coloring dyes, the content ratio is preferably 0.001% by weight to 5% by weight, more preferably 0.001% by weight to 3% by weight, and even more preferably 0.001% by weight to 1% by weight, from the viewpoint of further expressing the effect of the present invention.
[0061] In order to improve the peelability from the adhesive layer (1), the resin film (1) may have a release layer (1b). When the resin film (1) has a release layer (1b), the release layer (1b) side is directly laminated on the adhesive layer (1).
[0062] The forming material of the release layer (1b) can be any and appropriate forming material within the range that does not impair the effect of the present invention. As such forming material, for example, silicone-based release agents, fluorine-based release agents, long-chain alkyl-based release agents, fatty acid amide-based release agents, etc. can be listed. Among these, silicone-based release agents are preferred. The release layer (1b) can be formed in the form of a coating layer.
[0063] The thickness of the release layer (1b) may be any appropriate thickness according to the purpose within the range not impairing the effects of the present invention, and is preferably 10 nm to 1000 nm, more preferably 10 nm to 800 nm, further preferably 10 nm to 600 nm, and particularly preferably 10 nm to 500 nm.
[0064] The release layer (1b) may be composed of only one layer or two or more layers.
[0065] Examples of the silicone release layer include, for example, addition reaction type silicone resins. Specifically, examples of addition reaction type silicone resins include KS-774, KS-775, KS-778, KS-779H, KS-847H, and KS-847T manufactured by Shin-Etsu Chemical Co., Ltd.; TPR-6700, TPR-6710, and TPR-6721 manufactured by Toshiba Silicone Co., Ltd.; and SD7220 and SD7226 manufactured by Toray Dow Corning Co., Ltd. The coating amount of the silicone release layer (after drying) is preferably 0.01 g / m 2 ~2g / m 2 , more preferably 0.01 g / m 2 ~1g / m 2 , more preferably 0.01 g / m 2 ~0.5g / m2 .
[0066] The release layer (1b) can be formed by coating the above-mentioned forming material on any appropriate layer by a conventionally known coating method such as reverse gravure coating, bar coating, die coating, etc., and then performing a heat treatment at about 120 to 200° C. to cure the layer. In addition, a heat treatment and an active energy ray irradiation such as ultraviolet ray irradiation can be used in combination as necessary.
[0067] The resin film (1) may have an antistatic layer (1c).
[0068] The thickness of the antistatic layer (1c) may be any appropriate thickness within the range not impairing the effects of the present invention, preferably 1 nm to 500 nm, more preferably 5 nm to 300 nm, further preferably 7.5 nm to 200 nm, and particularly preferably 10 nm to 100 nm.
[0069] The antistatic layer (1c) may be composed of only one layer or two or more layers.
[0070] As the antistatic layer (1c), any and appropriate antistatic layer can be used within the scope of not damaging the effect of the present invention as long as it is a layer that can exert an antistatic effect. As such an antistatic layer, it is preferably an antistatic layer formed by coating a conductive coating liquid containing a conductive polymer on an arbitrary and appropriate substrate layer. Specifically, for example, an antistatic layer formed by coating a conductive coating liquid containing a conductive polymer on a resin substrate film (1a). As specific coating methods, roll coating, rod coating, gravure coating, etc. can be cited.
[0071] As the conductive polymer, any and appropriate conductive polymer can be used within the scope that does not damage the effect of the present invention. As such conductive polymer, for example, conductive polymers doped with polyanions in π-conjugated conductive polymers can be listed. As π-conjugated conductive polymers, chain conductive polymers such as polythiophene, polypyrrole, polyaniline, and polyacetylene can be listed. As polyanions, polystyrene sulfonic acid, polyisoprene sulfonic acid, polyvinyl sulfonic acid, polyallyl sulfonic acid, polyacrylic acid ethyl sulfonic acid, polymethacrylic acid, etc. can be listed. The conductive polymer can be only one kind, or it can be two or more kinds.
[0072] One embodiment of the resin film (1) comprises a resin base film (1a), an antistatic layer (1c) and a release layer (1b) in this order. Typically, this embodiment comprises a resin base film (1a), an antistatic layer (1c) and a release layer (1b).
[0073] Another embodiment of the resin film (1) comprises an antistatic layer (1c), a resin substrate film (1a), an antistatic layer (1c) and a release layer (1b) in this order. Typically, this embodiment is composed of an antistatic layer (1c), a resin substrate film (1a), an antistatic layer (1c) and a release layer (1b).
[0074] 《1-2. Adhesive layer (1)》
[0075] The adhesive layer (1) may be any appropriate adhesive layer as long as the effects of the present invention are not impaired. The adhesive layer (1) may be a single layer or may be two or more layers.
[0076] From the viewpoint of further exhibiting the effects of the present invention, the thickness of the adhesive layer (1) is preferably 5 μm to 75 μm, more preferably 5 μm to 60 μm, further preferably 7 μm to 50 μm, particularly preferably 7 μm to 40 μm, and most preferably 10 μm to 30 μm.
[0077] The adhesive layer (1) is preferably composed of at least one selected from the group consisting of acrylic adhesives, urethane adhesives, rubber adhesives, and silicone adhesives.
[0078] The adhesive layer (1) can be formed by any and appropriate method. As such method, for example, an adhesive composition (selected from at least one of the group consisting of an acrylic adhesive composition, a urethane adhesive composition, a rubber adhesive composition, and a silicone adhesive composition) is applied to any and appropriate substrate (for example, a resin film (2)), heated / dried as required, and cured as required to form an adhesive layer on the substrate. As such coating method, for example, a gravure roll coater, a reverse roll coater, a lick coater, a dip roll coater, a rod coater, a knife coater, an air knife coater, a spray coater, a comma coater, a direct coater, a roller brush coater, etc. can be cited.
[0079] The adhesive layer (1) may contain a conductive component. The conductive component may be one kind or two or more kinds.
[0080] The adhesive layer (1) may contain any appropriate additives within a range that does not impair the effects of the present invention. Such additives may be present in one type or in two or more types.
[0081] From the viewpoint of being able to further demonstrate the effects of the present invention, the adhesive layer (1) preferably contains at least one selected from the group consisting of a coloring pigment and a coloring dye as the above-mentioned additive. As the coloring pigment, a black pigment can be preferably cited. As the coloring dye, a black dye can be preferably cited. That is, as the above-mentioned additive in the adhesive layer (1), at least one selected from the group consisting of a black pigment and a black dye is more preferably cited.
[0082] When the adhesive layer (1) contains at least one selected from the group consisting of color pigments and color dyes, the content ratio of the at least one selected from the group consisting of color pigments and color dyes is preferably 0.01 wt % to 5 wt %, more preferably 0.01 wt % to 3 wt %, further preferably 0.05 wt % to 2 wt %, particularly preferably 0.08 wt % to 1.5 wt %, and most preferably 0.1 wt % to 1 wt % relative to the polymer component contained in the adhesive composition (at least one selected from the group consisting of acrylic adhesive composition, urethane adhesive composition, rubber adhesive composition, and silicone adhesive composition) forming the adhesive layer (1) from the viewpoint of further exhibiting the effect of the present invention. It should be noted that the "polymer component" mentioned herein refers to an acrylic polymer in the case of an acrylic adhesive composition, at least one selected from the group consisting of urethane prepolymers and polyols in the case of a urethane adhesive composition, a rubber polymer in the case of a rubber adhesive composition, and a silicone polymer in the case of a silicone adhesive composition.
[0083] <1-2-1. Acrylic Adhesive>
[0084] The acrylic adhesive is formed from an acrylic adhesive composition.
[0085] From the viewpoint of further expressing the effects of the present invention, the acrylic pressure-sensitive adhesive composition preferably contains an acrylic polymer and a crosslinking agent.
[0086] The acrylic polymer is referred to as a so-called base polymer in the field of acrylic pressure-sensitive adhesives. The acrylic polymer may be one type or two or more types.
[0087] The content of the acrylic polymer in the acrylic pressure-sensitive adhesive composition is preferably 60 to 99.9% by weight, more preferably 65 to 99.9% by weight, further preferably 70 to 99.9% by weight, particularly preferably 75 to 99.9% by weight, and most preferably 80 to 99.9% by weight, calculated on a solid basis.
[0088] As the acrylic polymer, any appropriate acrylic polymer may be adopted within a range not impairing the effects of the present invention.
[0089] From the viewpoint of further exhibiting the effects of the present invention, the weight average molecular weight of the acrylic polymer is preferably 300,000 to 2.5 million, more preferably 350,000 to 2 million, further preferably 400,000 to 1.8 million, particularly preferably 500,000 to 1.5 million.
[0090] From the viewpoint of further demonstrating the effects of the present invention, the acrylic polymer is preferably an acrylic polymer formed by polymerizing a composition (A) comprising (component a) an alkyl (meth)acrylate having 4 to 12 carbon atoms in the alkyl ester moiety, and (component b) at least one selected from the group consisting of (meth)acrylates having an OH group and (meth)acrylic acid. (component a) and (component b) may each independently be only one kind or may be two or more kinds.
[0091] As the alkyl (meth)acrylate (component a) in which the alkyl group of the alkyl ester moiety has 4 to 12 carbon atoms, for example, n-butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, etc. Among these, n-butyl (meth)acrylate and 2-ethylhexyl (meth)acrylate are preferred, and n-butyl acrylate and 2-ethylhexyl acrylate are more preferred, from the viewpoint of further exhibiting the effects of the present invention.
[0092] As at least one (component b) selected from the group consisting of (meth)acrylates and (meth)acrylic acid having an OH group, for example, (meth)acrylates having an OH group such as hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, and hydroxybutyl (meth)acrylate, (meth)acrylic acid, etc. can be cited. Among these, from the viewpoint of further exhibiting the effects of the present invention, hydroxyethyl (meth)acrylate and (meth)acrylic acid are preferred, and hydroxyethyl acrylate and acrylic acid are more preferred.
[0093] The composition (A) may contain a copolymerizable monomer other than the components (a) and (b). The copolymerizable monomer may be one kind or two or more kinds. Examples of such copolymerizable monomers include carboxyl group-containing monomers (excluding (meth)acrylic acid) such as itaconic acid, maleic acid, fumaric acid, crotonic acid, isocrotonic acid, and their anhydrides (e.g., monomers containing anhydride groups such as maleic anhydride and itaconic anhydride); amide group-containing monomers such as (meth)acrylamide, N,N-dimethyl(meth)acrylamide, N-hydroxymethyl(meth)acrylamide, N-methoxymethyl(meth)acrylamide, N-butoxymethyl(meth)acrylamide, and N-hydroxyethyl(meth)acrylamide; amino group-containing monomers such as aminoethyl(meth)acrylate, dimethylaminoethyl(meth)acrylate, and tert-butylaminoethyl(meth)acrylate; epoxy group-containing monomers such as glycidyl(meth)acrylate and methylglycidyl(meth)acrylate; cyano group-containing monomers such as acrylonitrile and methacrylonitrile; N-vinyl-2-pyrrolidone, (meth)acryloylmorpholine, N-vinylpiperidone, and N-vinylpiperazine , N-vinylpyrrole, N-vinylimidazole, vinylpyridine, vinylpyrimidine, vinyloxazole and other vinyl monomers containing heterocyclic rings; monomers containing sulfonic acid groups such as sodium vinyl sulfonate; monomers containing phosphate groups such as 2-hydroxyethyl acryloyl phosphate; monomers containing imide groups such as cyclohexylmaleimide and isopropylmaleimide; monomers containing isocyanate groups such as 2-methacryloyloxyethyl isocyanate; (meth)acrylates having alicyclic hydrocarbon groups such as cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, and isobornyl (meth)acrylate; (meth)acrylates having aromatic hydrocarbon groups such as phenyl (meth)acrylate, phenoxyethyl (meth)acrylate, and benzyl (meth)acrylate; vinyl esters such as vinyl acetate and vinyl propionate; aromatic vinyl compounds such as styrene and vinyltoluene; olefins and dienes such as ethylene, butadiene, isoprene, and isobutylene; vinyl ethers such as vinyl alkyl ether; vinyl chloride, etc.
[0094] As copolymerizable monomers, multifunctional monomers can also be used. Multifunctional monomers refer to monomers having two or more ethylenically unsaturated groups in one molecule. As ethylenically unsaturated groups, any and appropriate ethylenically unsaturated groups can be used within the scope that does not damage the effect of the present invention. As such ethylenically unsaturated groups, free radical polymerizable functional groups such as vinyl, propenyl, isopropenyl, vinyl ether (vinyloxy), allyl ether (allyloxy) can be listed. Examples of the multifunctional monomer include hexanediol di(meth)acrylate, butanediol di(meth)acrylate, (poly)ethylene glycol di(meth)acrylate, (poly)propylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, trimethylolpropane tri(meth)acrylate, tetramethylolmethane tri(meth)acrylate, allyl (meth)acrylate, vinyl (meth)acrylate, divinylbenzene, epoxy acrylate, polyester acrylate, and urethane acrylate. The multifunctional monomer may be one or more.
[0095] As the copolymerizable monomer, an alkoxyalkyl (meth)acrylate may also be used. Examples of the alkoxyalkyl (meth)acrylate include 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, methoxytriethylene glycol (meth)acrylate, 3-methoxypropyl (meth)acrylate, 3-ethoxypropyl (meth)acrylate, 4-methoxybutyl (meth)acrylate, and 4-ethoxybutyl (meth)acrylate. The alkoxyalkyl (meth)acrylate may be one or more.
[0096] From the viewpoint of further exhibiting the effects of the present invention, the content of the (meth)acrylic acid alkyl ester (component a) in which the alkyl group of the alkyl ester moiety has 4 to 12 carbon atoms is preferably 30 wt% or more, more preferably 35 to 99 wt%, further preferably 40 to 98 wt%, and particularly preferably 50 to 95 wt%, based on the total amount of monomer components constituting the acrylic polymer (100 wt%).
[0097] From the viewpoint of further exhibiting the effects of the present invention, the content of at least one (component b) selected from the group consisting of (meth)acrylates having an OH group and (meth)acrylic acid is preferably 1 wt% or more, more preferably 1 to 30 wt%, further preferably 2 to 20 wt%, and particularly preferably 3 to 10 wt%, based on the total amount (100 wt%) of the monomer components constituting the acrylic polymer.
[0098] Composition (A) can contain any and appropriate other components within the scope that does not damage the effect of the present invention. As such other components, for example, polymerization initiator, chain transfer agent, solvent etc. can be listed. The content of these other components can adopt any and appropriate content within the scope that does not damage the effect of the present invention.
[0099] The polymerization initiator may be a thermal polymerization initiator, a photopolymerization initiator (photoinitiator), etc., depending on the type of polymerization reaction. The polymerization initiator may be used alone or in combination of two or more.
[0100] The thermal polymerization initiator is preferably used when an acrylic polymer is obtained by solution polymerization. As such a thermal polymerization initiator, for example, an azo polymerization initiator, a peroxide polymerization initiator (for example, dibenzoyl peroxide, tert-butyl permaleate, etc.), a redox polymerization initiator, etc. can be cited. Among these thermal polymerization initiators, the azo initiator disclosed in Japanese Patent Publication No. 2002-69411 is particularly preferred. From the viewpoint that the decomposition product of the polymerization initiator is not easy to remain in the acrylic polymer as a part causing the generation of heating gas (degassing), such an azo polymerization initiator is preferred. As an azo polymerization initiator, 2,2'-azobisisobutyronitrile (hereinafter sometimes referred to as AIBN), 2,2'-azobis-2-methylbutyronitrile (hereinafter sometimes referred to as AMBN), 2,2'-azobis(2-methylpropionic acid) dimethyl ester, 4,4'-azobis-4-cyanovaleric acid, etc. can be cited.
[0101] The photopolymerization initiator is preferably used when obtaining an acrylic polymer by active energy ray polymerization. Examples of the photopolymerization initiator include benzoin ether photopolymerization initiators, acetophenone photopolymerization initiators, α-ketol photopolymerization initiators, aromatic sulfonyl chloride photopolymerization initiators, photoactive oxime photopolymerization initiators, benzoin photopolymerization initiators, benzyl photopolymerization initiators, benzophenone photopolymerization initiators, ketal photopolymerization initiators, and thioxanthone photopolymerization initiators.
[0102] Examples of benzoin ether-based photopolymerization initiators include benzoin methyl ether, benzoin ethyl ether, benzoin propyl ether, benzoin isopropyl ether, benzoin isobutyl ether, 2,2-dimethoxy-1,2-diphenylethane-1-one, and anisole methyl ether. Examples of acetophenone-based photopolymerization initiators include 2,2-diethoxyacetophenone, 2,2-dimethoxy-2-phenylacetophenone, 1-hydroxycyclohexyl phenyl ketone, 4-phenoxydichloroacetophenone, and 4-(tert-butyl)dichloroacetophenone. Examples of α-ketol-based photopolymerization initiators include 2-methyl-2-hydroxypropiophenone and 1-[4-(2-hydroxyethyl)phenyl]-2-methylpropane-1-one. Examples of aromatic sulfonyl chloride-based photopolymerization initiators include 2-naphthalenesulfonyl chloride. As photoactive oxime-based photopolymerization initiators, for example, 1-phenyl-1,1-propanedione-2-(o-ethoxycarbonyl)oxime, etc. can be listed. As benzoin-based photopolymerization initiators, for example, benzoin, etc. can be listed. As benzyl-based photopolymerization initiators, for example, benzyl, etc. can be listed. As benzophenone-based photopolymerization initiators, for example, benzophenone, benzoylbenzoic acid, 3,3'-dimethyl-4-methoxybenzophenone, polyvinylbenzophenone, α-hydroxycyclohexylphenylketone, etc. can be listed. As ketal-based photopolymerization initiators, for example, benzyldimethylketal, etc. can be listed. As thioxanthone-based photopolymerization initiators, for example, thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone, 2,4-dimethylthioxanthone, isopropylthioxanthone, 2,4-diisopropylthioxanthone, dodecylthioxanthone, etc. can be listed.
[0103] The acrylic adhesive composition may contain a crosslinking agent. By using a crosslinking agent, the cohesive force of the acrylic adhesive can be increased, and the effect of the present invention can be further demonstrated. The crosslinking agent may be only one kind or two or more kinds.
[0104] As the crosslinking agent, in addition to polyfunctional isocyanate crosslinking agents, epoxy crosslinking agents, melamine crosslinking agents, and peroxide crosslinking agents, urea crosslinking agents, metal alkoxide crosslinking agents, metal chelate crosslinking agents, metal salt crosslinking agents, carbodiimide crosslinking agents, oxazoline crosslinking agents, aziridine crosslinking agents, amine crosslinking agents, etc. can also be listed. Among these, from the viewpoint of being able to further demonstrate the effect of the present invention, at least one (component c) selected from the group consisting of polyfunctional isocyanate crosslinking agents and epoxy crosslinking agents is preferred.
[0105] Examples of the polyfunctional isocyanate crosslinking agent include lower aliphatic polyisocyanates such as 1,2-ethylene diisocyanate, 1,4-butylene diisocyanate, and 1,6-hexamethylene diisocyanate; alicyclic polyisocyanates such as cyclopentylene diisocyanate, cyclohexylene diisocyanate, isophorone diisocyanate, hydrogenated toluene diisocyanate, and hydrogenated xylene diisocyanate; and aromatic polyisocyanates such as 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 4,4′-diphenylmethane diisocyanate, and xylylene diisocyanate. Examples of the polyfunctional isocyanate crosslinking agent include commercially available products such as trimethylolpropane / toluene diisocyanate adduct (manufactured by Nippon Polyurethane Industries, Ltd., trade name “CORONATE L”), trimethylolpropane / hexamethylene diisocyanate adduct (manufactured by Nippon Polyurethane Industries, Ltd., trade name “CORONATE HL”), trade name “CORONATE HX” (Nippon Polyurethane Industries, Ltd.), and trimethylolpropane / xylylene diisocyanate adduct (manufactured by Mitsui Chemicals, Inc., trade name “TAKENATE 110N”).
[0106] Examples of epoxy crosslinking agents (polyfunctional epoxy compounds) include N,N,N',N'-tetraglycidyl-m-xylylenediamine, diglycidyl aniline, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, 1,6-hexanediol diglycidyl ether, neopentyl glycol diglycidyl ether, ethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, and sorbitol. Polyglycidyl ether, glycerol polyglycidyl ether, pentaerythritol polyglycidyl ether, polyglycerol polyglycidyl ether, sorbitan polyglycidyl ether, trimethylolpropane polyglycidyl ether, diglycidyl adipate, diglycidyl phthalate, triglycidyl-tris(2-hydroxyethyl)isocyanurate, resorcinol diglycidyl ether, bisphenol-S-diglycidyl ether, and epoxy resins having two or more epoxy groups in the molecule, etc. As epoxy crosslinking agents, commercial products such as trade name "TETRAD C" (manufactured by Mitsubishi Gas Chemical Co., Ltd.) can also be cited.
[0107] The content of the crosslinking agent in the acrylic adhesive composition can be any and appropriate within the range that does not impair the effect of the present invention. For example, from the viewpoint of further demonstrating the effect of the present invention, such content is preferably 0.05 to 20 parts by weight, more preferably 0.1 to 18 parts by weight, further preferably 0.5 to 15 parts by weight, and particularly preferably 0.5 to 10 parts by weight, relative to the solid content (100 parts by weight) of the acrylic polymer.
[0108] The acrylic adhesive composition may contain any and appropriate other components within the range that does not impair the effect of the present invention. Such other components include, for example, polymer components other than acrylic polymers, crosslinking accelerators, crosslinking catalysts, silane coupling agents, tackifying resins (rosin derivatives, polyterpene resins, petroleum resins, oil-soluble phenols, etc.), antioxidants, inorganic fillers, organic fillers, metal powders, colorants (pigments, dyes, etc.), foils, ultraviolet absorbers, antioxidants, light stabilizers, chain transfer agents, plasticizers, softeners, surfactants, antistatic agents, conductive agents, stabilizers, surface lubricants, leveling agents, preservatives, heat-resistant stabilizers, polymerization inhibitors, lubricants, solvents, catalysts, etc.
[0109] <1-2-2. Urethane Adhesive>
[0110] As the carbamate adhesive, any and appropriate carbamate adhesive such as the known carbamate adhesive described in Japanese Patent Publication No. 2017-039859 can be used within the scope that does not impair the effect of the present invention. As such a carbamate adhesive, for example, a carbamate adhesive formed by a carbamate adhesive composition, the carbamate adhesive composition includes at least one selected from the group consisting of a carbamate prepolymer and a polyol and a cross-linking agent. The carbamate adhesive may be only one kind or more than two kinds. The carbamate adhesive may contain any and appropriate components within the scope that does not impair the effect of the present invention.
[0111] <1-2-3. Rubber-based adhesive>
[0112] Typically, the rubber adhesive is formed by a rubber adhesive composition. Typically, the rubber adhesive composition includes a rubber polymer. As the rubber adhesive, any and appropriate rubber adhesive such as a known rubber adhesive described in Japanese Patent Application Publication No. 2015-074771 can be used within the scope that does not damage the effect of the present invention. They can be only one kind or two or more kinds. The rubber adhesive can contain any and appropriate components within the scope that does not damage the effect of the present invention.
[0113] <1-2-4. Silicone Adhesive>
[0114] Typically, the silicone adhesive is formed from a silicone adhesive composition. Typically, the silicone adhesive composition contains a silicone polymer. As the silicone adhesive, any and appropriate silicone adhesive such as the known silicone adhesives described in Japanese Patent Application Publication No. 2014-047280 can be used within the scope that does not impair the effect of the present invention. They can be only one kind or two or more kinds. The silicone adhesive can contain any and appropriate components within the scope that does not impair the effect of the present invention.
[0115] <1-2-5. Conductive component>
[0116] The adhesive layer (1) may contain a conductive component. Typically, the adhesive composition (at least one selected from the group consisting of an acrylic adhesive composition, a urethane adhesive composition, a rubber adhesive composition, and a silicone adhesive composition) that is the material of the adhesive layer (1) may contain a conductive component.
[0117] As the conductive component, any appropriate conductive component can be adopted within the range that does not impair the effects of the present invention. As such a conductive component, at least one compound selected from the group consisting of ionic liquids, ion conductive polymers, ion conductive fillers, and conductive polymers is preferred.
[0118] When the adhesive composition contains a conductive component, the ratio of the base polymer (e.g., acrylic polymer, polyol, urethane prepolymer, rubber polymer, silicone polymer) to the conductive component is preferably 0.01 to 10 parts by weight, more preferably 0.05 to 9.0 parts by weight, further preferably 0.075 to 8.0 parts by weight, and particularly preferably 0.1 to 7.0 parts by weight relative to 100 parts by weight of the base polymer.
[0119] As the ionic liquid, any appropriate ionic liquid may be adopted within the range not impairing the effects of the present invention. Here, the ionic liquid refers to a molten salt (ionic compound) that is liquid at 25° C. The ionic liquid may be one type or two or more types.
[0120] As such an ionic liquid, an ionic liquid composed of a fluorinated organic anion and an onium cation is preferred.
[0121] As the onium cation that can constitute the ionic liquid, any appropriate onium cation can be adopted within the range that does not impair the effect of the present invention. As such an onium cation, it is preferably at least one selected from nitrogen-containing onium cations, sulfur-containing onium cations, and phosphorus-containing onium cations.
[0122] As the onium cation that can constitute the ionic liquid, from the viewpoint of further exhibiting the effects of the present invention, it is preferred that the onium cation be at least one selected from cations having structures represented by general formulae (1) to (5).
[0123]
[0124] In the general formula (1), Ra represents a hydrocarbon group having 4 to 20 carbon atoms, optionally containing a heteroatom, and Rb and Rc are the same or different and represent hydrogen or a hydrocarbon group having 1 to 16 carbon atoms, optionally containing a heteroatom. In the case where the nitrogen atom contains a double bond, Rc is absent.
[0125] In the general formula (2), Rd represents a hydrocarbon group having 2 to 20 carbon atoms, which may contain a heteroatom, and Re, Rf and Rg are the same or different and represent hydrogen or a hydrocarbon group having 1 to 16 carbon atoms, which may contain a heteroatom.
[0126] In the general formula (3), Rh represents a hydrocarbon group having 2 to 20 carbon atoms, which may contain a heteroatom, and Ri, Rj and Rk are the same or different and represent hydrogen or a hydrocarbon group having 1 to 16 carbon atoms, which may contain a heteroatom.
[0127] In the general formula (4), Z represents a nitrogen atom, a sulfur atom or a phosphorus atom, and R1, Rm, Rn and Ro are the same or different and represent a hydrocarbon group having 1 to 20 carbon atoms, which may contain a hetero atom. When Z is a sulfur atom, Ro is absent.
[0128] In the general formula (5), X represents a Li atom, a Na atom or a K atom.
[0129] Examples of the cation represented by the general formula (1) include a pyridinium cation, a pyrrolidinium cation, a piperidinium cation, a cation having a pyrroline skeleton, and a cation having a pyrrole skeleton.
[0130] Specific examples of the cation represented by the general formula (1) include pyridinium cations such as 1-ethylpyridinium cation, 1-butylpyridinium cation, 1-hexylpyridinium cation, 1-ethyl-3-methylpyridinium cation, 1-butyl-3-methylpyridinium cation, 1-hexyl-3-methylpyridinium cation, 1-butyl-4-methylpyridinium cation, and 1-octyl-4-methylpyridinium cation; 1-ethyl-1-methylpyrrolidinium cation; ion, 1-methyl-1-propylpyrrolidinium cation, 1-methyl-1-butylpyrrolidinium cation, 1-methyl-1-pentylpyrrolidinium cation, 1-methyl-1-hexylpyrrolidinium cation, 1-methyl-1-heptylpyrrolidinium cation, 1-ethyl-1-propylpyrrolidinium cation, 1-ethyl-1-butylpyrrolidinium cation, 1-ethyl-1-pentylpyrrolidinium cation, 1-ethyl-1-hexylpyrrolidinium cation, 1-ethyl 1-methyl-1-ethylpiperidinium cation, 1-methyl-1-propylpiperidinium cation, 1-methyl-1-butylpiperidinium cation, 1-methyl-1-pentylpiperidinium cation, 1-methyl-1-hexylpiperidinium cation, 1-methyl-1-heptylpiperidinium cation, 1-ethyl-1-propylpiperidinium cation, 1-ethyl-1-butylpiperidinium cation, 1-methyl-1-pentylpiperidinium cation, 1-methyl-1-hexylpiperidinium cation, 1-methyl-1-heptylpiperidinium cation, 1-ethyl-1-propylpiperidinium cation, 1-ethyl-1-butylpiperidinium cation, 1-ethyl-1-pentylpiperidinium cation Piperidinium cations such as piperidinium cation, 1-ethyl-1-hexylpiperidinium cation, 1-ethyl-1-heptylpiperidinium cation, 1-propyl-1-butylpiperidinium cation, etc. are more preferably 1-hexylpyridinium cation, 1-ethyl-3-methylpyridinium cation, 1-butyl-3-methylpyridinium cation, 1-octyl-4-methylpyridinium cation, 1-methyl-1-propylpyrrolidinium cation, 1-methyl-1-propylpiperidinium cation.
[0131] Examples of the cation represented by the general formula (2) include an imidazolium cation, a tetrahydropyrimidinium cation, and a dihydropyrimidinium cation.
[0132] Specific examples of the cation represented by the general formula (2) include imidazolium cations such as 1,3-dimethylimidazolium cation, 1,3-diethylimidazolium cation, 1-ethyl-3-methylimidazolium cation, 1-butyl-3-methylimidazolium cation, 1-hexyl-3-methylimidazolium cation, 1-octyl-3-methylimidazolium cation, 1-decyl-3-methylimidazolium cation, 1-dodecyl-3-methylimidazolium cation, and 1-tetradecyl-3-methylimidazolium cation, and more preferably 1-ethyl-3-methylimidazolium cation and 1-hexyl-3-methylimidazolium cation.
[0133] Examples of the cation represented by the general formula (3) include a pyrazolium cation and a pyrazolinium cation.
[0134] Specific examples of the cation represented by the general formula (3) include pyrazolium cations such as 1-methylpyrazolium cation, 3-methylpyrazolium cation, 1-ethyl-2-methylpyrazolinium cation, 1-ethyl-2,3,5-trimethylpyrazolium cation, 1-propyl-2,3,5-trimethylpyrazolium cation, and 1-butyl-2,3,5-trimethylpyrazolium cation; pyrazolium cations such as 1-ethyl-2,3,5-trimethylpyrazolium cation, 1-propyl-2,3,5-trimethylpyrazolium cation, and 1-butyl-2,3,5-trimethylpyrazolium cation; and the like.
[0135] Examples of the cation represented by the general formula (4) include tetraalkylammonium cations, trialkylsulfonium cations, tetraalkylphosphonium cations, and cations in which a part of the above alkyl groups is substituted with an alkenyl group, an alkoxy group, or an epoxy group.
[0136] Specific examples of the cation represented by the general formula (4) include, for example, triethylmethylammonium cation, tributylethylammonium cation, trimethyldecylammonium cation, diethylmethylsulfonium cation, dibutylethylsulfonium cation, dimethyldecylammonium cation, triethylmethylphosphonium cation, tributylethylphosphonium cation, trimethyldecylammonium cation and the like asymmetric tetraalkylammonium cations; trialkylsulfonium cations, tetraalkylphosphonium cations, N,N-diethyl-N-methyl-N-(2-methoxyethyl)ammonium cations, glycidyltrimethylammonium cations, diallyldimethylammonium cations, N,N-dimethyl- N-ethyl-N-propylammonium cation, N,N-dimethyl-N-ethyl-N-butylammonium cation, N,N-dimethyl-N-ethyl-N-pentylammonium cation, N,N-dimethyl-N-ethyl-N-hexylammonium cation, N,N-dimethyl-N-ethyl-N-heptylammonium cation, N,N-dimethyl-N-ethyl-N-nonylammonium cation, N,N-dimethyl-N,N-dipropylammonium cation, N,N-diethyl-N-propyl-N-butylammonium cation, N,N-dimethyl-N-propyl-N-pentylammonium cation, N,N-dimethyl-N-propyl-N-hexylammonium cation N,N-dimethyl-N-propyl-N-heptylammonium cation, N,N-dimethyl-N-butyl-N-hexylammonium cation, N,N-diethyl-N-butyl-N-heptylammonium cation, N,N-dimethyl-N-pentyl-N-hexylammonium cation, N,N-dimethyl-N,N-dihexylammonium cation, trimethylheptylammonium cation, N,N-diethyl-N-methyl-N-propylammonium cation, N,N-diethyl-N-methyl-N-pentylammonium cation, N,N-diethyl-N-methyl-N-heptylammonium cation, N,N-diethyl-N-propyl-N-pentylammonium cation, The cations include triethylpropylammonium cation, triethylpentylammonium cation, triethylheptylammonium cation, N,N-dipropyl-N-methyl-N-ethylammonium cation, N,N-dipropyl-N-methyl-N-pentylammonium cation, N,N-dipropyl-N-butyl-N-hexylammonium cation, N,N-dipropyl-N,N-dihexylammonium cation, N,N-dibutyl-N-methyl-N-pentylammonium cation, N,N-dibutyl-N-methyl-N-hexylammonium cation, trioctylmethylammonium cation, and N-methyl-N-ethyl-N-propyl-N-pentylammonium cation, and the like, with trimethylpropylammonium cation being more preferred.
[0137] As the fluorinated organic anion that can constitute the ionic liquid, any appropriate fluorinated organic anion can be adopted within the range not impairing the effects of the present invention. Such fluorinated organic anion may be completely fluorinated (perfluorinated) or partially fluorinated.
[0138] Examples of such fluorinated organic anions include perfluoroalkylsulfonates, bis(fluorosulfonyl)imides, and bis(perfluoroalkanesulfonyl)imides. More specifically, examples include trifluoromethanesulfonates, pentafluoroethanesulfonates, heptafluoropropanesulfonates, nonafluorobutanesulfonates, bis(fluorosulfonyl)imides, and bis(trifluoromethanesulfonyl)imides.
[0139] As a specific example of an ionic liquid, it can be appropriately selected and used from the combination of the above-mentioned cationic component and the above-mentioned anionic component. As a specific example of such an ionic liquid, for example, 1-hexylpyridinium bis (fluorosulfonyl) imide, 1-ethyl-3-methylpyridinium trifluoromethanesulfonate, 1-ethyl-3-methylpyridinium pentafluoroethanesulfonate, 1-ethyl-3-methylpyridinium heptafluoropropanesulfonate, 1-ethyl-3-methylpyridinium nonafluorobutanesulfonate, 1-butyl-3-methylpyridinium trifluoromethanesulfonate, 1-butyl-3-methylpyridinium bis (trifluoromethanesulfonyl) imide, 1-octyl-4-methylpyridinium bis (fluorosulfonyl) imide, 1-methyl-1-propylpyrrolidinium bis (trifluoromethanesulfonyl) imide, 1-methyl-1-propylpyrrolidinium bis (trifluoromethanesulfonyl) imide, 1-methyl-1-propylpyridin ... Pyrrolidinium bis(fluorosulfonyl)imide, 1-methyl-1-propylpiperidinium bis(trifluoromethanesulfonyl)imide, 1-methyl-1-propylpiperidinium bis(fluorosulfonyl)imide, 1-ethyl-3-methylimidazolium trifluoromethanesulfonate, 1-ethyl-3-methylimidazolium heptafluoropropanesulfonate, 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide, 1-ethyl-3-methylimidazolium bis(fluorosulfonyl)imide, 1-hexyl-3-methylimidazolium bis(fluorosulfonyl)imide, trimethylpropylammonium bis(trifluoromethanesulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide.
[0140] Ionic liquids can use commercial products, or they can be synthesized by the following operation. As the synthesis method of ionic liquids, there is no particular limitation as long as the target ionic liquid can be obtained. Generally speaking, the halide method, hydroxide method, acid ester method, complex formation method, and neutralization method described in the document "Ionic Liquids - The Forefront and Future of Development -" (published by CMC) can be used.
[0141] Hereinafter, the synthesis methods of nitrogen-containing onium salts are described using halide method, hydroxide method, acid ester method, complex formation method and neutralization method as examples. Other ionic liquids such as sulfur-containing onium salts and phosphorus-containing onium salts can also be obtained using the same methods.
[0142] The halide method is a method using reactions such as those shown in reaction formulas (1) to (3). First, a tertiary amine is reacted with a halide alkyl to obtain a halide (in reaction formula (1), chlorine, bromine or iodine is used as the halogen).
[0143] The obtained halide is reacted with an acid (HA) or a salt (MA; M is a cation such as ammonium, lithium, sodium, potassium, etc. that forms a salt with the target anion) having the anion structure (A-) of the target ionic liquid to obtain the target ionic liquid (R4NA).
[0144] (1)R3N+RX→R4N×(X: Cl, Br, I)
[0145] (2) R4NX+HA→R4NA+HX
[0146] (3)R4NX+MA→R4NA+MX (M: NH4, Li, Na, K, Ag, etc.)
[0147] The hydroxide method is a method performed by reactions such as those shown in reaction formulas (4) to (8). First, a halide (R4NX) is electrolyzed by an ion exchange membrane method (reaction formula (4)), an OH-type ion exchange resin method (reaction formula (5)), or reacted with silver oxide (Ag2O) (reaction formula (6)) to obtain a hydroxide (R4NOH) (chlorine, bromine, or iodine is used as the halogen).
[0148] The obtained hydroxide is subjected to the reaction of reaction formulas (7) to (8) in the same manner as in the above-mentioned halogenation method to obtain the target ionic liquid (R4NA).
[0149] (4)R4NX+H2O→R4NOH+1 / 2H2+1 / 2X2(X: Cl, Br, I)
[0150] (5) R4NX+P-OH→R4NOH+PX (P-OH: OH type ion exchange resin)
[0151] (6)R4NX+1 / 2Ag2O+1 / 2H2O→R4NOH+AgX
[0152] (7) R4NOH+HA→R4NA+H2O
[0153] (8)R4NOH+MA→R4NA+MOH (M: NH4, Li, Na, K, Ag, etc.)
[0154] The acid ester method is a method carried out by reactions such as those shown in reaction formulas (9) to (11). First, a tertiary amine (R3N) is reacted with an acid ester to obtain an acid ester (in reaction formula (9), as the acid ester, esters of inorganic acids such as sulfuric acid, sulfurous acid, phosphoric acid, phosphorous acid, and carbonic acid; esters of organic acids such as methanesulfonic acid, methylphosphonic acid, and formic acid can be used).
[0155] The obtained acid ester is subjected to the reaction of reaction formulas (10) to (11) in the same manner as the above-mentioned halogenation method to obtain the target ionic liquid (R4NA). In addition, an ionic liquid can also be directly obtained by using methyl trifluoromethanesulfonate, methyl trifluoroacetate, etc. as the acid ester.
[0156] (9) R3N+ROY→R4NOY
[0157]
[0158] (10) R4NOY+HA→R4NA+HOY
[0159]
[0160] (11)R4NOY+MA→R4NA+MOY (M: NH4, Li, Na, K, Ag, etc.)
[0161] The neutralization method is a method performed by a reaction as shown in reaction formula (12), and can be obtained by reacting a tertiary amine with an organic acid such as CF3COOH, CF3SO3H, (CF3SO2)2NH, (CF3SO2)3CH, or (C2F5SO2)2NH.
[0162] (12)R3N+HZ→R3HN + Z - [HZ: organic acids such as CF3COOH, CF3SO3H, (CF3SO2)2NH, (CF3SO2)3CH, (C2F5SO2)2NH]
[0163] In the above reaction formulae (1) to (12), R represents hydrogen or a hydrocarbon group having 1 to 20 carbon atoms, and may contain a hetero atom.
[0164] As the ion conductive polymer, any and appropriate ion conductive polymer can be used within the scope that does not damage the effect of the present invention. As such ion conductive polymer, for example, ion conductive polymers obtained by polymerizing or copolymerizing monomers having quaternary ammonium salt groups; conductive polymers such as polythiophene, polyaniline, polypyrrole, polyethyleneimine, and allylamine polymers can be listed. The ion conductive polymer can be only one kind or two or more kinds.
[0165] As the ion conductive filler, any and appropriate ion conductive filler can be used within the range that does not impair the effect of the present invention. As such ion conductive filler, for example, tin oxide, antimony oxide, indium oxide, cadmium oxide, titanium oxide, zinc oxide, indium, tin, antimony, gold, silver, copper, aluminum, nickel, chromium, titanium, iron, cobalt, copper iodide, ITO (indium oxide / tin oxide), ATO (antimony oxide / tin oxide), etc. can be listed. The ion conductive filler can be only one kind or two or more kinds.
[0166] As the conductive polymer, any appropriate conductive polymer may be adopted within the range not impairing the effects of the present invention. Examples of such conductive polymers include (3,4-ethylenedioxythiophene)-poly(styrenesulfonic acid) and the like.
[0167] <1-2-6. Other ingredients>
[0168] The adhesive composition (at least one selected from the group consisting of acrylic adhesive composition, urethane adhesive composition, rubber adhesive composition, and silicone adhesive composition) that is the material of the adhesive layer (1) may contain any and appropriate other components within the range that does not impair the effect of the present invention. Examples of such other components include other polymer components, crosslinking accelerators, crosslinking catalysts, silane coupling agents, tackifying resins (rosin derivatives, polyterpene resins, petroleum resins, oil-soluble phenols, etc.), antioxidants, inorganic fillers, organic fillers, metal powders, colorants (pigments, dyes, etc.), foils, ultraviolet absorbers, antioxidants, light stabilizers, chain transfer agents, plasticizers, softeners, surfactants, antistatic agents, conductive agents, stabilizers, surface lubricants, leveling agents, preservatives, heat stabilizers, polymerization inhibitors, lubricants, solvents, catalysts, etc.
[0169] 《1-3. Resin film (2)》
[0170] The thickness of the resin film (2) can be any appropriate thickness according to the purpose within the range that does not impair the effect of the present invention. From the viewpoint of further demonstrating the effect of the present invention, the thickness is preferably 20 μm to 125 μm, more preferably 25 μm to 100 μm, further preferably 38 μm to 100 μm, particularly preferably 40 μm to 80 μm, and most preferably 50 μm to 75 μm.
[0171] The resin film (2) includes a resin base film (2a).
[0172] Examples of the resin substrate film (2a) include plastic films made of polyester resins such as polyethylene terephthalate (PET), polyethylene naphthalate (PEN), and polybutylene terephthalate (PBT); plastic films made of olefin resins having α-olefins as monomer components such as polyethylene (PE), polypropylene (PP), polymethylpentene (PMP), ethylene-propylene copolymers, and ethylene-vinyl acetate copolymers (EVA); plastic films made of polyvinyl chloride (PVC); plastic films made of vinyl acetate resins; and plastic films made of polycarbonate. Plastic films composed of polytetrafluoroethylene, polychlorotrifluoroethylene, polyvinyl fluoride, polyvinylidene fluoride, tetrafluoroethylene-hexafluoropropylene copolymer, chlorofluoroethylene-vinylidene fluoride copolymer, etc.
[0173] The resin base film (2a) may be a single layer or may be a plurality of layers. The resin base film (2a) may be stretched.
[0174] The resin substrate film (2a) may be subjected to a surface treatment, such as corona treatment, plasma treatment, chromic acid treatment, ozone exposure, flame exposure, high voltage electric shock exposure, ionizing radiation treatment, primer coating treatment, and the like.
[0175] The resin substrate film (2a) may contain any and appropriate additives within the scope that does not damage the effect of the present invention. However, from the viewpoint that the effect of the present invention can be further demonstrated, the content of the additives in the resin substrate film (2a) is preferably 5% by weight or less, more preferably 3% by weight or less, further preferably 1% by weight or less, particularly preferably 0.5% by weight or less, and most preferably substantially 0% by weight. Here, "substantially 0% by weight" means that the trace impurity content within the scope that does not damage the effect of the present invention can be ignored.
[0176] As the additive, for example, at least one selected from the group consisting of a coloring pigment and a coloring dye can be cited. As the coloring pigment, a black pigment can be preferably cited. As the coloring dye, a black dye can be preferably cited.
[0177] When the resin base film (2a) contains at least one selected from the group consisting of coloring pigments and coloring dyes, its content ratio is preferably 0.001% by weight to 5% by weight, more preferably 0.001% by weight to 3% by weight, and further preferably 0.001% by weight to 1% by weight, from the viewpoint of further expressing the effect of the present invention.
[0178] The resin film (2) may include a conductive layer (2b). The conductive layer (2b) may be disposed between the adhesive layer (1) and the resin base film (2a).
[0179] The conductive layer (2b) may be only one layer or may be two or more layers.
[0180] The conductive layer (2b) can be provided by forming it on any appropriate substrate. As such a substrate, a resin substrate film (2a) is preferred.
[0181] Regarding the conductive layer (2b), a conductive film is formed on any and appropriate substrate (preferably a resin substrate film (2a)) by any and appropriate thin film forming method such as vacuum evaporation, sputtering, ion plating, spray pyrolysis, chemical plating, electroplating, or a combination thereof. Among these thin film forming methods, vacuum evaporation and sputtering are preferred from the viewpoints of the formation speed of the conductive film, the formability of a large-area film, productivity, etc.
[0182] As materials for forming a conductive film, for example, metal materials including gold, silver, platinum, palladium, copper, aluminum, nickel, chromium, titanium, iron, cobalt, tin, alloys thereof, etc.; metal oxide materials including indium oxide, tin oxide, titanium oxide, cadmium oxide, mixtures thereof, etc.; other metal compounds including copper iodide, etc. can be used.
[0183] As the thickness of the conductive layer (2b), any appropriate thickness can be adopted according to the purpose within the range that does not impair the effect of the present invention. As such a thickness, for example, when it is formed of a metal material, it is preferably When formed of a metal oxide material, it is preferably
[0184] The surface resistance value of the conductive layer (2b) is preferably 1.0×10 10 Ω / □ or less, more preferably 1.0×10 9 Ω / □ or less, more preferably 1.0×10 8 Ω / □ or less, particularly preferably 1.0×10 7 Ω / □ or less.
[0185] When a conductive film is formed on any and appropriate substrate (preferably a resin substrate film (2a)), the surface of the substrate (preferably a resin substrate film (2a)) may be subjected to any and appropriate pretreatment such as corona discharge treatment, ultraviolet irradiation treatment, plasma treatment, sputtering etching treatment, primer treatment, etc., which can also improve the adhesion between the conductive film and the substrate (preferably a resin substrate film (2a)).
[0186] The resin film (2) may have an antistatic layer (2c). The antistatic layer (2c) may be disposed between the adhesive layer (1) and the resin base film (2a) and / or between the resin base film (2a) and the adhesive layer (2).
[0187] The antistatic layer (2c) may be composed of only one layer or two or more layers.
[0188] The thickness of the antistatic layer (2c) can be any and appropriate thickness according to the purpose within the scope of not damaging the effect of the present invention. As such thickness, it is preferably 1nm to 1000nm, more preferably 5nm to 900nm, further preferably 7.5nm to 800nm, and particularly preferably 10nm to 700nm.
[0189] The surface resistance value of the antistatic layer (2c) is preferably 1.0×10 10 Ω / □ or less, more preferably 8.0×10 9 Ω / □ or less, more preferably 5.0×10 9 Ω / □ or less, particularly preferably 1.0×10 9 Ω / □ or less.
[0190] As antistatic layer (2c), as long as it is a layer that can exert antistatic effect, any and appropriate antistatic layer can be adopted in the scope that does not damage the effect of the present invention. As this antistatic layer, it is preferably an antistatic layer formed by coating a conductive coating liquid comprising a conductive polymer on any and appropriate substrate layer. Specifically, for example, an antistatic layer formed by coating a conductive coating liquid comprising a conductive polymer on a resin substrate film (2a). After coating, it is dried as required, and curing treatment (heat treatment, ultraviolet treatment, etc.) is performed as required. As specific coating method, roll coating, rod coating, gravure coating, etc. can be listed.
[0191] As the conductive coating liquid containing a conductive polymer, any and appropriate conductive coating liquid can be used within the scope of not damaging the effect of the present invention. Such a conductive coating liquid preferably contains a conductive polymer, a binder, a cross-linking agent and a solvent. The solvent evaporates, evaporates, etc. by heating, etc. in the process of forming the antistatic layer (2c), thereby substantially disappearing, therefore, the antistatic layer (2c) preferably contains a conductive polymer, a binder and a cross-linking agent.
[0192] Examples of the solvent include organic solvents, water, and mixed solvents thereof. Examples of the organic solvent include esters such as ethyl acetate, ketones such as methyl ethyl ketone, acetone, and cyclohexanone, cyclic ethers such as tetrahydrofuran (THF) and dioxane, aliphatic or alicyclic hydrocarbons such as n-hexane and cyclohexane, aromatic hydrocarbons such as toluene and xylene, aliphatic or alicyclic alcohols such as methanol, ethanol, n-propanol, isopropanol, and cyclohexanol, and glycol ethers such as alkylene glycol monoalkyl ethers (e.g., ethylene glycol monomethyl ether, ethylene glycol monoethyl ether), and dialkylene glycol monoalkyl ethers. As the solvent, water or a mixed solvent having water as the main component (e.g., a mixed solvent of water and ethanol) is preferred.
[0193] The content of the conductive polymer in the antistatic layer (2c) is preferably 3% by weight to 80% by weight, more preferably 5% by weight to 60% by weight.
[0194] As the conductive polymer, any and appropriate conductive polymer can be used within the scope that does not impair the effect of the present invention. As such conductive polymer, for example, conductive polymers in which polyanions are doped in π-conjugated conductive polymers can be cited. As π-conjugated conductive polymers, chain conductive polymers such as polythiophene, polypyrrole, polyaniline, and polyacetylene can be cited. As polyanions, polystyrene sulfonic acid, polyisoprene sulfonic acid, polyvinyl sulfonic acid, polyallyl sulfonic acid, polyethyl acrylate sulfonic acid, polymethacrylic acid, etc. can be cited.
[0195] The conductive polymer may be used alone or in combination of two or more.
[0196] The content of the binder in the antistatic layer (2c) is preferably 50% by weight to 95% by weight, more preferably 60% by weight to 90% by weight.
[0197] As a binder that can be included in the conductive coating liquid, any and appropriate binder can be used within the range that does not impair the effect of the present invention. The binder can be only one kind or two or more kinds. As such a binder, a resin is preferably used, and a polyester resin is more preferably used. The proportion of the polyester resin in the binder is preferably 90% by weight to 100% by weight, and more preferably 98% by weight to 100% by weight.
[0198] The polyester resin preferably contains polyester as a main component (preferably more than 50% by weight, more preferably 75% by weight or more, further preferably 90% by weight or more, and particularly preferably a component occupying substantially 100% by weight).
[0199] As the polyester, any and appropriate polyester can be used within the range that does not impair the effect of the present invention. As such a polyester, it is preferred to have a structure obtained by condensing one or more compounds (polycarboxylic acid components) selected from polycarboxylic acids (e.g., dicarboxylic acid compounds) and derivatives thereof (e.g., anhydrides, esters, halides, etc. of polycarboxylic acids) having two or more carboxyl groups in one molecule and one or more compounds (polyol components) selected from polyols (e.g., diols) having two or more hydroxyl groups in one molecule.
[0200] As the polycarboxylic acid component, any appropriate polycarboxylic acid can be adopted within a range not impairing the effects of the present invention. Examples of such polycarboxylic acid components include aliphatic dicarboxylic acids such as oxalic acid, malonic acid, difluoromalonic acid, alkylmalonic acid, succinic acid, tetrafluorosuccinic acid, alkylsuccinic acid, (±)-malic acid, mesotartaric acid, itaconic acid, maleic acid, methylmaleic acid, fumaric acid, methylfumaric acid, acetylenedicarboxylic acid, glutaric acid, hexafluoroglutaric acid, methylglutaric acid, glutaconic acid, adipic acid, dithioadipic acid, methyladipic acid, dimethyladipic acid, tetramethyladipic acid, methyleneadipic acid, muconic acid, galactaric acid, pimelic acid, suberic acid, perfluorosuberic acid, 3,3,6,6-tetramethylsuberic acid, azelaic acid, sebacic acid, perfluorosebacic acid, brassic acid, dodecyldicarboxylic acid, tridecyldicarboxylic acid, and tetradecyldicarboxylic acid; and cycloalkyldicarboxylic acids (e.g., 1,4-cyclohexanedicarboxylic acid). alicyclic dicarboxylic acids such as phthalic acid, isophthalic acid, dithioisophthalic acid, methylisophthalic acid, dimethylisophthalic acid, chloroisophthalic acid, dichloroisophthalic acid, terephthalic acid, methylterephthalic acid, dimethylterephthalic acid, chloroterephthalic acid, bromoterephthalic acid, naphthalene dicarboxylic acid, oxofluorene dicarboxylic acid, anthracene dicarboxylic acid, biphenyl dicarboxylic acid, biphenyl dicarboxylic acid, dimethyl biphenyl dicarboxylic acid, 4,4"-p-terphenyl dicarboxylic acid, 4,4"-p-quaterphenyl dicarboxylic acid, bibenzyl dicarboxylic acid, azobenzene dicarboxylic acid, and o-carboxyphenyl acetic acid (Homophthalic Aromatic dicarboxylic acids such as terephthalic acid, ...
[0201] As the polycarboxylic acid component, preferably listed are aromatic dicarboxylic acids and their anhydrides such as terephthalic acid, isophthalic acid, and naphthalene dicarboxylic acid; aliphatic dicarboxylic acids and their anhydrides such as adipic acid, sebacic acid, azelaic acid, succinic acid, fumaric acid, maleic acid, HIMIC acid, and 1,4-cyclohexane dicarboxylic acid; lower alkyl esters of these dicarboxylic acids (for example, esters formed with monohydric alcohols having 1 to 3 carbon atoms), etc.
[0202] As the polyol component, any and appropriate polyol can be used within the range that does not impair the effect of the present invention. Examples of such polyol components include glycols such as ethylene glycol, propylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,3-butylene glycol, 1,4-butylene glycol, neopentyl glycol, 1,5-pentanediol, 1,6-hexanediol, 3-methylpentanediol, diethylene glycol, 1,4-cyclohexanedimethanol, 3-methyl-1,5-pentanediol, 2-methyl-1,3-propanediol, 2,2-diethyl-1,3-propanediol, 2-butyl-2-ethyl-1,3-propanediol, o-phthalic alcohol, hydrogenated bisphenol A, and bisphenol A; and alkylene oxide adducts of these glycols (e.g., ethylene oxide adducts, propylene oxide adducts, etc.).
[0203] The molecular weight of the polyester resin is preferably a weight average molecular weight (Mw) in terms of standard polystyrene measured by gel permeation chromatography (GPC) of 5×10 3 ~1.5×10 5 , more preferably 1×10 4 ~6×10 4 .
[0204] The glass transition temperature (Tg) of the polyester resin is preferably 0°C to 120°C, more preferably 10°C to 80°C.
[0205] As the polyester resin, for example, commercially available polyester resins such as "VYLONAL" manufactured by Toyobo Co., Ltd. can be used.
[0206] The conductive coating liquid may further contain a resin other than the polyester resin (for example, at least one resin selected from acrylic resins, acrylic urethane resins, acrylic styrene resins, acrylic silicone resins, silicone resins, polysilazane resins, polyurethane resins, fluororesins, and polyolefin resins) as a binder within a range that does not impair the effects of the present invention.
[0207] As the cross-linking agent that can be included in the conductive coating liquid, any and appropriate cross-linking agent can be adopted within the scope of not damaging the effect of the present invention. The cross-linking agent can be only one kind, or it can be more than two kinds. As such a cross-linking agent, preferably an isocyanate cross-linking agent, an epoxy cross-linking agent, a melamine cross-linking agent, a peroxide cross-linking agent, and a urea cross-linking agent, a metal alkoxide cross-linking agent, a metal chelate cross-linking agent, a metal salt cross-linking agent, a carbodiimide cross-linking agent, an oxazoline cross-linking agent, an aziridine cross-linking agent, an amine cross-linking agent, etc. can be listed. Among them, a melamine cross-linking agent is preferred.
[0208] The content of the crosslinking agent in the antistatic layer (2c) is preferably 1% by weight to 30% by weight, more preferably 2% by weight to 20% by weight.
[0209] The antistatic layer (2c) may contain any appropriate other components within a range not impairing the effects of the present invention.
[0210] 《1-4. Optional other layers》
[0211] The laminate according to the embodiment of the present invention may have any and appropriate other layers in addition to the resin film (1), the adhesive layer (1) and the resin film (2). Such other layers may be only one layer or two or more layers.
[0212] In the laminate according to the embodiment of the present invention, other layers are typically as follows: Figure 2 As shown, examples thereof include an adhesive layer (2) and a resin film (3).
[0213] <1-4-1. Adhesive Layer (2)>
[0214] The adhesive layer (2) may be any appropriate adhesive layer as long as the effects of the present invention are not impaired. The adhesive layer (2) may be a single layer or may be two or more layers.
[0215] From the viewpoint of further exhibiting the effects of the present invention, the thickness of the adhesive layer (2) is preferably 0.5 μm to 150 μm, more preferably 1 μm to 100 μm, further preferably 2 μm to 80 μm, particularly preferably 3 μm to 50 μm, and most preferably 5 μm to 30 μm.
[0216] The adhesive layer (2) is preferably composed of at least one selected from the group consisting of acrylic adhesives, urethane adhesives, rubber adhesives, and silicone adhesives.
[0217] The adhesive layer (2) can be formed by any and appropriate method. As such method, for example, an adhesive composition (selected from at least one of the group consisting of an acrylic adhesive composition, a urethane adhesive composition, a rubber adhesive composition, and a silicone adhesive composition) is applied to any and appropriate substrate (for example, a resin film (3)), heated / dried as required, and cured as required to form an adhesive layer on the substrate. As such coating method, for example, methods such as a gravure roll coater, a reverse roll coater, a lick coater, a dip roll coater, a rod coater, a knife coater, an air knife coater, a spray coater, a comma coater, a direct coater, and a roller brush coater can be cited.
[0218] The adhesive layer (2) may contain a conductive component. Regarding the conductive component, the description in the item <1-2-5. Conductive component> can be directly referred to.
[0219] The adhesive layer (2) may contain any appropriate additives within a range that does not impair the effects of the present invention. Such additives may be present in one type or in two or more types.
[0220] As the above-mentioned additive, for example, at least one selected from the group consisting of a coloring pigment and a coloring dye can be listed. As the coloring pigment, a black pigment can be preferably listed. As the coloring dye, a black dye can be preferably listed. That is, as the above-mentioned additive, at least one selected from the group consisting of a black pigment and a black dye is preferred.
[0221] When the adhesive layer (2) contains at least one selected from the group consisting of color pigments and color dyes, the content ratio of the at least one selected from the group consisting of color pigments and color dyes is preferably 0.01% by weight to 5% by weight, more preferably 0.1% by weight to 3% by weight, and even more preferably 0.5% by weight to 1% by weight relative to the polymer component contained in the adhesive composition (typically, an acrylic adhesive composition) forming the adhesive layer (2) from the viewpoint of further exhibiting the effect of the present invention. It should be noted that the "polymer component" mentioned herein refers to an acrylic polymer in the case of an acrylic adhesive composition, at least one selected from the group consisting of a urethane prepolymer and a polyol in the case of a urethane adhesive composition, a rubber polymer in the case of a rubber adhesive composition, and a silicone polymer in the case of a silicone adhesive composition.
[0222] Regarding acrylic adhesives, urethane adhesives, rubber adhesives, and silicone adhesives, the descriptions in <1-2-1. Acrylic adhesive>, <1-2-2. Urethane adhesive>, <1-2-3. Rubber adhesive>, and <1-2-4. Silicone adhesive> can be directly referred to, respectively.
[0223] The adhesive composition (at least one selected from the group consisting of acrylic adhesive composition, urethane adhesive composition, rubber adhesive composition, and silicone adhesive composition) that is the material of the adhesive layer (2) may contain any and appropriate other components within the range that does not impair the effects of the present invention. As such other components, the description in <1-2-6. Other components> can be directly cited.
[0224] <1-4-2. Resin film (3)>
[0225] From the viewpoint of further demonstrating the effects of the present invention, the thickness of the resin film (3) is preferably 4 μm to 450 μm, more preferably 8 μm to 350 μm, further preferably 12 μm to 250 μm, particularly preferably 16 μm to 150 μm, and most preferably 20 μm to 100 μm.
[0226] Regarding the resin film (3), the description in the item "1-3. Resin film (2)" can be directly cited.
[0227] 《《2. Method for producing a laminate》》
[0228] The laminate according to the embodiment of the present invention can be produced by any appropriate method within the range that the effects of the present invention are not impaired.
[0229] As a representative example of the method for manufacturing a laminate according to an embodiment of the present invention, the laminate of the present invention is described as a laminate having a resin film (1), an adhesive layer (1), and a resin film (2) in sequence and including these technical features.
[0230] When the laminate described in the embodiment of the present invention is a laminate having a resin film (1), an adhesive layer (1), and a resin film (2) in sequence and including these technical features, as a manufacturing method thereof, for example, an adhesive composition (selected from at least one of the group consisting of an acrylic adhesive composition, a urethane adhesive composition, a rubber adhesive composition, and a silicone adhesive composition) forming an adhesive constituting the adhesive layer (1) can be applied to the resin film (2), heated / dried as needed, and cured as needed to form the adhesive layer (1) on the resin film (2), and then the resin film (1) is attached to the surface of the adhesive layer (1) on the opposite side to the resin film (2) (when a release layer (1b) is present, it is the release layer side) to manufacture the laminate.
[0231] As another representative example of the method for manufacturing a laminate described in an embodiment of the present invention, the case where the laminate of the present invention is a laminate having a lipid film (1), an adhesive layer (1), a resin film (2), an adhesive layer (2), and a resin film (3) in sequence and containing these technical features is described.
[0232] When the laminate described in the embodiment of the present invention is a laminate having a resin film (1), an adhesive layer (1), a resin film (2), an adhesive layer (2), and a resin film (3) in sequence and including these technical features, as a manufacturing method thereof, for example, a laminate (A) having a resin film (1), an adhesive layer (1), and a resin film (2) in sequence and including these technical features and a laminate (B) having an adhesive layer (2) and a resin film (3) in sequence and including these technical features are manufactured respectively, and then the surface of the resin film (2) of the laminate (A) is pasted to the surface of the adhesive layer (2) of the laminate (B).
[0233] The laminate (A) can be produced, for example, by the following operation: an adhesive composition (selected from at least one of the group consisting of an acrylic adhesive composition, a urethane adhesive composition, a rubber adhesive composition, and a silicone adhesive composition) forming an adhesive constituting the adhesive layer (1) is applied onto a resin film (2), heated / dried as required, and cured as required to form the adhesive layer (1) on the resin film (2), and then affixed to the surface of the adhesive layer (1) on the opposite side to the resin film (2) (when a release layer (1b) is present, it is the release layer side).
[0234] The laminate (B) is prepared by, for example, applying an adhesive composition (preferably an acrylic adhesive composition) which forms an adhesive constituting the adhesive layer (2) onto a resin film (3), heating / drying the adhesive as required, and curing the adhesive as required, thereby forming the adhesive layer (2) on the resin film (3).
[0235] In the period until the laminate (A) and the laminate (B) are bonded together, an arbitrary and appropriate separator (for example, the same film as the resin film (1)) may be bonded in advance in order to protect the exposed surface of the adhesive layer (2).
[0236] 《《3. Method for manufacturing image display component》》
[0237] The laminate of the present invention is used in the method for producing the image display member according to the embodiment of the present invention.
[0238] The laminate of the present invention used in the method for producing an image display member according to the embodiment of the present invention is obtained by directly laminating a resin film (1) and a pressure-sensitive adhesive layer (1).
[0239] The manufacturing method of the image display component according to the embodiment of the present invention comprises: a step of peeling off the resin film (1) from the adhesive layer (1), and a step of laminating the OLED panel on the exposed adhesive layer (1). As the peeling method and laminating method, any and appropriate method can be adopted within the range that does not impair the effect of the present invention.
[0240] The method for producing an image display member according to the embodiment of the present invention can produce an image display member in which an OLED panel is laminated on the adhesive layer (1) side of a laminate A obtained by peeling off a resin film (1) from the laminate of the present invention.
[0241] In the image display member according to the embodiment of the present invention, since the laminated body of the present invention is used, it is possible to exhibit excellent inspection properties from the back side in the production process.
[0242] 《《4. Manufacturing method of mobile electronic device》》
[0243] In the method for manufacturing a mobile electronic device according to the embodiment of the present invention, the laminated body of the present invention is used.
[0244] The laminate of the present invention used in the method for producing a mobile electronic device according to the embodiment of the present invention is a laminate in which a resin film (1) and an adhesive layer (1) are directly laminated.
[0245] The manufacturing method of the mobile electronic device described in the embodiment of the present invention includes: the process of peeling off the resin film (1) from the adhesive layer (1); the process of laminating the OLED panel on the exposed adhesive layer (1); the process of setting the adhesive layer (2) on the outermost layer of the laminated body on the side of the resin film (2) when observed from the self-adhesive layer (1); and the process of laminating the shell on the side of the adhesive layer (2) opposite to the side where the resin film (2) exists. As the order of each process, any and appropriate order can be adopted within the scope that does not damage the effect of the present invention. As the peeling method, laminating method, and method of setting the adhesive layer, any and appropriate method can be adopted within the scope that does not damage the effect of the present invention.
[0246] As the adhesive layer (2), any appropriate adhesive layer can be adopted within a range not impairing the effects of the present invention.
[0247] By using the manufacturing method of a mobile electronic device described in an embodiment of the present invention, it is possible to manufacture a mobile electronic device in which an OLED panel is laminated on the adhesive layer (1) side of a laminate A obtained by peeling off a resin film (1) from the laminate of the present invention, and the self-adhesive layer (1) of the laminate A is observed as the outermost layer on the resin film (2) side and is adhered to a housing with the aid of the adhesive layer (2).
[0248] In the mobile electronic device according to the embodiment of the present invention, by using the laminate of the present invention, it is possible to exhibit both excellent inspection performance from the back side during the manufacturing process and excellent antireflection performance for preventing reflection from the observation side of the obtained mobile electronic device.
[0249] Example
[0250] Hereinafter, the present invention will be specifically described by examples, but the present invention is not limited to these examples at all. It should be noted that the test and evaluation methods in the examples etc. are as follows. It should be noted that when it is recorded as "parts", it means "parts by weight" as long as there is no special record, and when it is recorded as "%", it means "% by weight" as long as there is no special record.
[0251] <Measurement of Weight Average Molecular Weight>
[0252] The weight average molecular weight was measured by gel permeation chromatography (GPC). Specifically, a GPC measuring apparatus using a trade name "HLC-8120GPC" (manufactured by Tosoh Corporation) was used, and the measurement was performed under the following conditions, and the weight average molecular weight was calculated based on a standard polystyrene conversion value.
[0253] (Molecular weight measurement conditions)
[0254] Sample concentration: 0.2 wt% (tetrahydrofuran solution)
[0255] Sample injection volume: 10μL
[0256] Column: Trade name "TSKguardcolumn SuperHZ-H (1 piece) + TSKgel SuperHZM-H (2 pieces)" (manufactured by Tosoh Corporation)
[0257] Reference column: Trade name "TSKgel SuperH-RC (1 column)" (manufactured by Tosoh Corporation)
[0258] ·Eluent: Tetrahydrofuran (THF)
[0259] Flow rate: 0.6mL / min
[0260] Detector: Differential Refractometer (RI)
[0261] Column temperature (measurement temperature): 40°C
[0262] <Determination of total light transmittance>
[0263] The total light transmittance was measured using HM-150N from Murakami Color Research Laboratory under the conditions of JIS-K-7361. At this time, the laminate was arranged so that the resin film (2) (or the resin film (3) if the resin film (3) was provided) faced the light source side.
[0264] <Anti-reflective property confirmation>
[0265] The peeling resin film on one side of a double-sided tape (CS9660TB, total light transmittance>87%, manufactured by Nitto Denko Corporation) having a three-layer structure of a peeling resin film-optical acrylic adhesive-peeling resin film is peeled off and applied to the surface side of the resin film (2) (or the resin film (3) when having an adhesive layer (2) and a resin film (3)) of the laminate (I) to be measured. Thereafter, the remaining peeling resin film is peeled off, and an aluminum foil (manufactured by Mitsubishi Aluminum Corporation) is cut into a size about half that of the flat side of the laminate (I) and applied to the optical acrylic adhesive on the laminate (I) to be measured. Next, the resin film (1) is peeled off from the laminate (I). A polyimide resin film ("UPILEX-50S", thickness 50 μm, manufactured by Ube Industries) was laminated to the exposed adhesive layer (1), and then a polarizing film ("REGQ1698GDUHC3+H2-BW", thickness 78 μm, manufactured by Nitto Denko Corporation) was laminated to the polyimide resin film. The polarizing film was placed on a test bench so that the surface side thereof was facing upward. Figure 3 As shown, the antireflection property was checked in the vertical direction from a distance of 30 cm from the polarizing plate. The judgment was made based on whether the portion with the aluminum foil attached and the portion without the aluminum foil attached could be clearly distinguished.
[0266] 0:Cannot distinguish clearly.
[0267] ×: Can be clearly distinguished.
[0268] <Inspection Confirmation>
[0269] Peel off the resin film (1) from the laminate (I) to be measured. Stick the exposed adhesive layer (1) on the magic-printed side of the laminate (II) of a magic-printed polyimide resin film ("UPILEX-50S", thickness 50 μm, manufactured by Ube Industries, Ltd.) and a polarizing film ("REGQ1698GDUHC3+H2-BW", thickness 78 μm, manufactured by Nitto Denko Corporation). Set it on the sample stage of a digital microscope (VHX200, manufactured by Keyence Corporation) in such a way that the surface side of the polarizing plate is facing downward. Set the magnification of the microscope lens to 10 times and focus, as shown in FIG. Figure 4 As shown, the magic print of the polyimide resin film was confirmed. The judgment was made based on whether the magic print was observed.
[0270] ○: Printing observed.
[0271] ×: No printing was observed.
[0272] [Manufacturing Example 1]: Manufacture of Adhesive Composition A1
[0273] Into a reaction vessel equipped with a thermometer, a stirrer, a reflux condenser and a nitrogen inlet tube, 63 parts by weight of 2-ethylhexyl acrylate (2EHA) as monomers, 15 parts by weight of N-vinyl pyrrolidone (NVP), 9 parts by weight of methyl methacrylate (MMA) and 13 parts by weight of hydroxyethyl acrylate (HEA), 0.2 parts by weight of azobisisobutyronitrile as a polymerization initiator, and 233 parts by weight of ethyl acetate as a solvent were added, and nitrogen was circulated and nitrogen replacement was performed for about 1 hour while stirring. Thereafter, the mixture was heated to 60°C and reacted for 7 hours to obtain an acrylic polymer solution having a weight average molecular weight (Mw) of 1.2 million. 1 part by weight of TAKENATED 110N (Mitsui Chemicals) was added to the obtained acrylic polymer solution relative to 100 parts by weight of the acrylic polymer, and the mixture was uniformly mixed and further reacted to obtain a solution of acrylic polymer A.
[0274] To the obtained solution of acrylic polymer A, 1 part by weight of a black pigment (carbon black manufactured by Alfa Aesar) was added based on 100 parts by weight of acrylic polymer A to prepare a black adhesive composition A1.
[0275] [Manufacturing Example 2]: Manufacture of Adhesive Composition A2
[0276] To the solution of acrylic polymer A obtained in Production Example 1, 1.5 parts by weight of a black pigment (carbon black manufactured by Alfa Aesar) was added based on 100 parts by weight of acrylic polymer A to prepare a black adhesive composition A2.
[0277] [Manufacturing Example 3]: Manufacture of Adhesive Composition A3
[0278] The solution of acrylic polymer A obtained in Production Example 1 itself was made into PSA composition A3.
[0279] [Manufacturing Example 4]: Manufacture of Adhesive Composition A4
[0280] To the solution of acrylic polymer A obtained in Production Example 1, 3 parts by weight of a black pigment (carbon black manufactured by Alfa Aesar) was added based on 100 parts by weight of acrylic polymer A to prepare a black adhesive composition A4.
[0281] [Example 1]
[0282] The release resin film on one side of a double-sided tape (with a total light transmittance of 80%, manufactured by Tomogawa Paper) having a three-layer structure of release resin film-acrylic adhesive-release resin film was peeled off, and the tape was laminated to the non-antistatic treated surface of a base material formed of polyester resin ("T910J75", thickness 75 μm, manufactured by Mitsubishi Chemical Corporation). Next, the remaining release resin film was peeled off, and the tape was laminated to the silicone treated surface of a base material formed of polyester resin ("MRQ50T100J", thickness 50 μm, manufactured by Mitsubishi Chemical Corporation) treated with silicone.
[0283] Through the above operation, a stacked body 1 having a total light transmittance of 80% is obtained, which is composed of a resin film (1-1) (with a silicone treated surface) (thickness 50 μm) / adhesive layer (1-1) (thickness 25 μm) / resin film (2-1) (thickness 75 μm).
[0284] The results are shown in Table 1.
[0285] [Example 2]
[0286] Instead of using a double-sided tape having a three-layer structure of a peeling resin film - an acrylic adhesive - a peeling resin film (having a total light transmittance of 80%, manufactured by Tomogawa Paper Co., Ltd.), a double-sided tape having a three-layer structure of a peeling resin film - an acrylic adhesive - a peeling resin film (having a total light transmittance of 75%, manufactured by Tomogawa Paper Co., Ltd.) was used. Except for this, the same procedure as in Example 1 was used to obtain a laminate 2 having a total light transmittance of 75%, a resin film (1-2) (with a silicone-treated surface) (thickness 50 μm) / adhesive layer (1-2) (thickness 25 μm) / resin film (2-2) (thickness 75 μm).
[0287] The results are shown in Table 1.
[0288] [Example 3]
[0289] Instead of using a double-sided tape having a three-layer structure of a peeling resin film - an acrylic adhesive - a peeling resin film (with a total light transmittance of 80%, manufactured by Tomokawa Paper Co., Ltd.), a double-sided tape having a three-layer structure of a peeling resin film - an acrylic adhesive - a peeling resin film (with a total light transmittance of 69%, manufactured by Tomokawa Paper Co., Ltd.) was used. Except for this, the same procedure as in Example 1 was used to obtain a laminate 3 having a structure of a resin film (1-3) (with a silicone-treated surface) (thickness 50 μm) having a total light transmittance of 69% / adhesive layer (1-3) (thickness 25 μm) / resin film (2-3) (thickness 75 μm).
[0290] The results are shown in Table 1.
[0291] [Example 4]
[0292] Instead of using a double-sided tape having a three-layer structure of a peeling resin film - an acrylic adhesive - a peeling resin film (having a total light transmittance of 80%, manufactured by Tomokawa Paper Co., Ltd.), a double-sided tape having a three-layer structure of a peeling resin film - an acrylic adhesive - a peeling resin film (having a total light transmittance of 59%, manufactured by Tomokawa Paper Co., Ltd.) was used. Except for this, the same procedure as in Example 1 was followed to obtain a laminate 4 having a structure of a resin film (1-4) (with a silicone-treated surface) (50 μm thick) having a total light transmittance of 59%) / an adhesive layer (1-4) (25 μm thick) / a resin film (2-4) (75 μm thick) having a total light transmittance of 59%.
[0293] The results are shown in Table 1.
[0294] [Example 5]
[0295] Instead of using a double-sided tape having a three-layer structure of a peeling resin film - an acrylic adhesive - a peeling resin film (having a total light transmittance of 80%, manufactured by Tomokawa Paper Co., Ltd.), a double-sided tape having a three-layer structure of a peeling resin film - an acrylic adhesive - a peeling resin film (having a total light transmittance of 49%, manufactured by Tomokawa Paper Co., Ltd.) was used. Except for this, the same procedure as in Example 1 was followed to obtain a laminate 5 having a structure of a resin film (1-5) (with a silicone-treated surface) (50 μm thick) having a total light transmittance of 49% / adhesive layer (1-5) (25 μm thick) / resin film (2-5) (75 μm thick) having a total light transmittance of 49%.
[0296] The results are shown in Table 1.
[0297] [Example 6]
[0298] The adhesive composition A1 obtained in Manufacturing Example 1 was applied to a substrate formed of a polyester resin ("Lumirror S10", thickness 75 μm, manufactured by Toray Industries, Inc.) using an impregnation roller in a manner such that the thickness after drying becomes 25 μm, and cured and dried under the conditions of a drying temperature of 130°C and a drying time of 2 minutes. In this manner, an adhesive layer was prepared on the substrate. Next, the silicone-treated surface of the substrate formed of a polyester resin ("Lumirror S10", thickness 25 μm, manufactured by Toray Industries, Inc.) having one surface subjected to silicone treatment was attached to the surface of the adhesive layer to obtain a laminate 6 having a structure of a resin film (1-6) (with a silicone-treated surface) (thickness 25 μm) / adhesive layer (1-6) (thickness 25 μm) / resin film (2-6) (thickness 75 μm) having a total light transmittance of 30%.
[0299] The results are shown in Table 1.
[0300] [Example 7]
[0301] Instead of the adhesive composition A1 obtained in Manufacturing Example 1, the adhesive composition A2 obtained in Manufacturing Example 2 was used. Otherwise, the same procedure as in Example 6 was carried out to obtain a stacked body 7 having a structure of a resin film (1-7) (with a silicone-treated surface) (thickness 25 μm) / adhesive layer (1-7) (thickness 25 μm) / resin film (2-7) (thickness 75 μm) having a total light transmittance of 21%.
[0302] The results are shown in Table 1.
[0303] [Comparative Example 1]
[0304] Instead of the adhesive composition A1 obtained in Manufacturing Example 1, the adhesive composition A3 obtained in Manufacturing Example 3 was used. Otherwise, the same procedure as in Example 6 was carried out to obtain a stacked body C1 having a total light transmittance of 87% and consisting of a resin film (1-C1) (with a silicone-treated surface) (thickness 25 μm) / adhesive layer (1-C1) (thickness 25 μm) / resin film (2-C1) (thickness 75 μm).
[0305] The results are shown in Table 1.
[0306] [Comparative Example 2]
[0307] Instead of the adhesive composition A1 obtained in Manufacturing Example 1, the adhesive composition A4 obtained in Manufacturing Example 4 was used. Otherwise, the same procedure as in Example 6 was carried out to obtain a stacked body C2 having a total light transmittance of 5% and consisting of a resin film (1-C2) (with a silicone-treated surface) (thickness 25 μm) / adhesive layer (1-C2) (thickness 25 μm) / resin film (2-C2) (thickness 75 μm).
[0308] The results are shown in Table 1.
[0309] [Table 1]
[0310] Total light transmittance Anti-reflective Inspection Example 1 80 ○ ○ Example 2 75 ○ ○ Example 3 69 ○ ○ Example 4 59 ○ ○ Example 5 49 ○ ○ Example 6 30 ○ ○ Example 7 21 ○ ○ Comparative Example 1 87 × ○ Comparative Example 2 5 ○ ×
[0311] Industrial Applicability
[0312] The laminated body of the present invention can be suitably used in the production process of optical components and electronic components, and the like.
[0313] Description of Reference Numerals
[0314] Resin film (1) 10
[0315] Adhesive layer (1) 20
[0316] Resin film (2) 30
[0317] Adhesive layer (2) 40
[0318] Resin film (3) 50
[0319] Optical acrylic adhesive layer 60
[0320] Polyimide resin film 70
[0321] Printing unit 75
[0322] Polarizing film 80
[0323] Aluminum Foil 90
[0324] Laminated body 100
Claims
1. A laminate comprising three or more layers, in this order: a resin film (1), an adhesive layer (1), and a resin film (2), The total light transmittance of the laminate is 20% to 83%.
2. A method for producing an image display member, which is a method for producing an image display member using the laminate according to claim 1, wherein: The resin film (1) is directly laminated with the adhesive layer (1), and the manufacturing method comprises: A step of peeling the resin film (1) from the adhesive layer (1); and A step of laminating an OLED panel onto the exposed adhesive layer (1).
3. A method for manufacturing a mobile electronic device, which is a method for manufacturing a mobile electronic device using the laminate according to claim 1, wherein: The resin film (1) is directly laminated with the adhesive layer (1), and the manufacturing method comprises: A step of peeling the resin film (1) from the adhesive layer (1); A step of laminating an OLED panel on the exposed adhesive layer (1); A step of providing an adhesive layer (2) on the outermost layer of the laminate on the side of the resin film (2) as viewed from the adhesive layer (1); and A step of bonding a housing to the side of the adhesive layer (2) opposite to the side where the resin film (2) is present.
Citation Information
Patent Citations
Laminate
CN103249555A
Adhesive Sheet Used For Graphite Flake
CN106916543A
Back surface adhesion film and dicing tape-combined back surface adhesion film
CN110544665A
Cohesive film for protection of optical sheet before inspection and method for manufacturing optical sheet using the same
JP2002328226A
Method of manufacturing image display device and image display device manufactured by using the method
JP2009175266A
